Study of the IL-4 and IL-4δ2 interaction with the IL-4R receptors of the I and II types in silico and the effect on the functional activity of mononuclear cells in vitro - K. V. Goremykin; A. N. Silkov; B. V. Shilov; V. Yu. Serebrov; A. E. Sazonov; S. V. Sennikov (Бюллетень сибирской медицины, 2010)
Alternatively spliced interleukins are very actively studied over the last years. Splice form of IL-4 — IL-4δ2 has antagonistic effects to its full form on proliferative activity of human mononuclear blood cells and their IL-6 production. Antagonistic effects between IL-4 and IL-4δ2 were confirmed and explained in this study due to combination of biochemical and computer methods.